Identifying the trade-offs between climate change mitigation and adaptation in urban land use planning: An empirical study in a coastal city. (December 2019) - Xu, Lilai; Wang, Xiaoming; Liu, Jiahui; He, Yuanrong; Tang, Jianxiong; Nguyen, Minh; Cui, Shenghui
Abstract: Cities play a significant role in climate change mitigation and adaptation. Urban land planning shapes the urban form and is considered to be an effective approach for climate change mitigation and adaptation. Yet, there is little knowledge about what urban forms can reduce both greenhouse gas (GHG) emissions and climate stresses while considering trade-offs between them. Here, we investigate the role of urban land use in both climate change mitigation and adaptation. In particular, we assess quantitatively the competition between strategies for mitigation and adaptation and identify potential win-win solutions in land use responses. Using a coastal city as a case study, we find that the land use strategies for unilateral mitigation or adaptation can cause contradicting consequences with respect to the reductions in GHG emissions and climate stresses, i.e. reductions in GHGs could increase climate stresses or vice versa. Poorly integrated strategies potentially may compromise international efforts to meet the Climate Action in the Sustainable Development Goals. Properly integrated mitigation and adaptation strategies, or climate-sensitive land use planning, however, can lead to win-win outcomes and eventually achieve co-benefits. Yet, any co-benefits will gradually diminish if there is a delay in climate-sensitive land use planning, implying growing GHGs and intensified climate stresses. Our analysis indicates that integrating climate change mitigation and adaptation in urban land use needs to be enacted as soon as possible: any delays in implementation reduce the window to act to maximize the co-benefits. Highlights: Investigating the trade-offs between mitigation and adaptation in urban land use Land use strategies for unilateral mitigation or adaptation can cause contradicting consequences. Urban land use integrating mitigation and adaptation can lead to win-win outcomes. Win-win outcomes will diminish if climate-sensitive land use planning is delayed. Integrating mitigation and adaptation in urban land use need to be enacted now.